Expectancy changes the self‐monitoring of voice identity. (26th March 2021) - Johnson, Joseph F.; Belyk, Michel; Schwartze, Michael; Pinheiro, Ana P.; Kotz, Sonja A.
Abstract: Self‐voice attribution can become difficult when voice characteristics are ambiguous, but functional magnetic resonance imaging (fMRI) investigations of such ambiguity are sparse. We utilized voice‐morphing (self‐other) to manipulate (un‐)certainty in self‐voice attribution in a button‐press paradigm. This allowed investigating how levels of self‐voice certainty alter brain activation in brain regions monitoring voice identity and unexpected changes in voice playback quality. FMRI results confirmed a self‐voice suppression effect in the right anterior superior temporal gyrus (aSTG) when self‐voice attribution was unambiguous. Although the right inferior frontal gyrus (IFG) was more active during a self‐generated compared to a passively heard voice, the putative role of this region in detecting unexpected self‐voice changes during the action was demonstrated only when hearing the voice of another speaker and not when attribution was uncertain. Further research on the link between right aSTG and IFG is required and may establish a threshold monitoring voice identity in action. The current results have implications for a better understanding of the altered experience of self‐voice feedback in auditory verbal hallucinations. Abstract : FMRI results confirmed a self‐voice suppression effect in the right anterior superior temporal gyrus (aSTG) when self‐voice attribution was unambiguous. Although the right inferior frontal gyrus (IFG) was more active during self‐generated compared to passively‐heard voice, the putative role of this region in detecting unexpected self‐voice changes during the action was demonstrated only when hearing the voice of another speaker and not when attribution was uncertain.